1999
DOI: 10.1029/1999rs900043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the protonosphere on the estimation of GPS total electron content: Validation using model simulations

Abstract: Abstract. Simulated observations of total electron cornera (TEC) along ray paths from Global Positiomng System (GPS) satellites have been used to validate the estimation of TEC using GPS measuremeres. The Sheffield Umversity plasmasphere ionosphere model (SUPIM) has been used to create electron densities that were integrated along ray paths from actual configurations of the GPS constellation. The resultant slant electron contents were then used as inputs to validate the self-calibration of pseudo-range errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 12 publications
(3 reference statements)
7
51
0
Order By: Relevance
“…4. Other research has found that the distribution of the plasmaspheric electron content along the meridional line has a significant effect on TEC and GPS instrumental bias estimation, and the accuracy of the instrumental bias can be improved by properly considering the distribution of the plasmaspheric electron content (Lunt et al, 1999;Mazzella et al, 2002Mazzella et al, , 2007Mazzella et al, , 2009Anghel et al, 2009;Carrano et al, 2009). Based on this improvement the distribution of the plasmaspheric electron content was estimated using GPS measurements (Mazzella et al, 2002(Mazzella et al, , 2007Anghel et al, 2009;Carrano et al, 2009).…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…4. Other research has found that the distribution of the plasmaspheric electron content along the meridional line has a significant effect on TEC and GPS instrumental bias estimation, and the accuracy of the instrumental bias can be improved by properly considering the distribution of the plasmaspheric electron content (Lunt et al, 1999;Mazzella et al, 2002Mazzella et al, , 2007Mazzella et al, , 2009Anghel et al, 2009;Carrano et al, 2009). Based on this improvement the distribution of the plasmaspheric electron content was estimated using GPS measurements (Mazzella et al, 2002(Mazzella et al, , 2007Anghel et al, 2009;Carrano et al, 2009).…”
Section: Results and Analysismentioning
confidence: 99%
“…4 gradually increases and the accuracy becomes worse with latitude decreasing. Certainly, the influence of the distribution of the plasmasphere along the meridional line in the lower latitude on the estimation of the instrumental bias should also be noted (Lunt et al, 1999;Mazzella et al, 2007). Although this brings about the complication for the interpretation of these results, further study to distinguish their influences can increase undoubtedly the accuracy of the ionospheric and plasmaspheric TEC from GPS observations.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations